2011
DOI: 10.1007/s12231-011-9154-3
|View full text |Cite
|
Sign up to set email alerts
|

Yarrow (Achillea millefolium L.): A Neglected Panacea? A Review of Ethnobotany, Bioactivity, and Biomedical Research1

Abstract: Yarrow (Achillea millefolium L.): A Neglected Panacea? A Review of Ethnobotany, Bioactivity, and Biomedical Research. Yarrow (Achillea millefolium L.) is one of the most widely used medicinal plants in the world, primarily for wounds, digestive problems, respiratory infections, and skin conditions, and secondarily, among other uses, for liver disease and as a mild sedative. Preclinical studies indicate that it may have anti-inflammatory, anti-ulcer, hepatoprotective, anxiolytic, and perhaps antipathogenic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 76 publications
1
63
0
1
Order By: Relevance
“…As there might be some new implications for A. millefolium in preventing or treating mental disorders [2], the result of present study demonstrated that long term treatment with aqueous extract of A. millefolium has no impairing effect of recognition memory in mice.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…As there might be some new implications for A. millefolium in preventing or treating mental disorders [2], the result of present study demonstrated that long term treatment with aqueous extract of A. millefolium has no impairing effect of recognition memory in mice.…”
Section: Resultssupporting
confidence: 52%
“…In several studies, various doses of A. mellifolium extracts ranging from 8 to 3000 mg/kg were used. However, the most frequent doses for A. millefolium extracts were between 50 to 1000 mg/kg [2].…”
Section: Data Are Expressed As Mean ± Sem; T2 Results Were Obtainedmentioning
confidence: 99%
See 1 more Smart Citation
“…In Traditional Chinese Medicine (TCM), the flowers of Achillea species has been used for a variety of conditions such as bleeding, wounds, haemorrhoids, varicose veins, dysmenorrhoea and tuberculosis condition (3). In the entire American continent, the most important uses were for skin problems and injuries, bleeding conditions, respiratory illnesses, digestive problems, toothaches and eye problems (14). Karamenderes and Apaydin demonstrated that ethanol extract Achillea micrantha exhibits an inhibitory effect on the dose-response curves induced by acetylcholine and CaCl 2 on rat duodenum (13).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Achillea is represented by about 110-140 species mostly found in Europe and Asia and a few species native to northern Africa and North America 1 .About forty species of Achillea are located in Turkey 2 . Edirne is one of the places where members of Achillea family are located in yarrow particularly.…”
Section: Introductionmentioning
confidence: 99%